SIGNS OF SOCIO-POLITICAL VOCABULARY AND INTERACTION WITH SOCIO-POLITICAL TERMINOLOGY (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2022)
This article provides information about signs of socio-political vocabulary and its interaction with socio-political terminology. In addition, this article demonstrates the features of the socio-political vocabulary and the socio-political terminology, their interaction, similarities and differences.